How In The World? A Fascinating journey through the world of human ingenuity - Reader's Digest Association (U.S.A Reader's Digest Association, 1990)
This fascinating reference answers those "How in the world do they do that?" questions with engrossing explanations of the principles behind the most important technological achievements of the past and present. Twelve absorbing sections and over 1,200 illustrations, cover the full range of man's ingenuity, the heights of his inventiveness.